Physiological and skill fitness differences of professional footballers: Position of play - Moses, M. O.; Sarpong, P. A.; Collins, B. O. (European Journal of Sports & Exercise Science, 2015)
The international federation of football history and statistics ranked Asante Kotoko Sporting Club as the African club of the 20th century. This study examined if this pedigree inform the physiological and skill fitness qualities of the club`s players based on position of play. Twenty-five regular players (mean ± SD age, 23.26 ± 2.57 years) were categorised into nine playing positions participated in the study. Players` body mass index, heart rate and blood pressures were measured and also speed (30meter dash); agility (Illinois agility run) and muscular endurance (Burpee) were tested. Players significantly possessed selected physiological and skill fitness qualities (p<0.05). Based on position of play, differences in the selected qualities were not significant except in muscular endurance [F (8, 16) =3.151, p<0.05]. Holding midfielders returned higher speed (6.56±0.58 seconds); centre-forwarders had best agility score (18.05 ±0.93seconds); and goalkeepers had the highest muscular endurance score (35.67 ±0.57 rpm). Players` training patterns appeared to lack developmental approaches through positional specificity. Athletic trainers and the coaching crew should structure training specificity fitness programs focusing on agility, speed and muscular endurance of the players in order to improve their skills in relation to positions of play